Does doing "good" always translate into doing "well"? An eco‐efficiency perspective. (2nd May 2019) - Broadstock, David C.; Managi, Shunsuke; Matousek, Roman; Tzeremes, Nickolaos G.
Abstract: Does doing "good" always translate into doing "well"? Debate over the "value" of corporate social responsibility is high on the agenda of corporate finance research. Deeper understanding is required on managers' incentives to pursue and implement corporate social responsibility related strategies, as is more thorough comprehension of the effect of these strategies to firms' performance levels as well as shareholder and wider stakeholder valuations of the firm. This paper provides a new lens by approaching the subject from a different methodological paradigm, grounded in the performance benchmarking methods more commonly applied in operational research. In so doing, we provide novel evidence of the effect of corporate choices on environmental, social, and governance (ESG) strategic investment compliance (i.e., doing good) to firms' eco‐efficiency levels (doing well). In brief, our empirical findings suggest that ESG and firm's eco‐performance are nonlinearly related. Specifically, advanced ESG policies and disclosure levels are associated with a positive affect to firms' eco‐efficiency levels, but only up to a point, after which the effect becomes "neutral, " that is, ESG demonstrates a visible pattern of diminishing marginal returns. Thus, we may humbly conclude that a firm may "do well" by doing good, but it is not clear they should ever expect to "do great" just by "doing good." The threshold at which this "neutrality" appears varies systematically with the characteristics of the sector in which the firm is operating, as well as dimensions of board diversity. Finally, it is evident that ESG implementation choices can be a source of managerial agency problems.